2019
DOI: 10.1002/ijgo.12942
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes and markers of cesarean delivery among Colombian women

Abstract: Objective: To investigate the association of socioeconomic status (SES) components (education, occupation, and household wealth) with number (1 or ≥2) and timing (planned/emergency) of cesarean delivery (CD) in Colombia, rates of which are well above the levels recommended by the World Health Organization. Methods:A cross-sectional study using the 2015 Demographic and Health Survey (DHS) of Colombia was carried out; 38 718 women answered the woman only module.Binomial and multinomial logistic regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 9 publications
0
10
0
3
Order By: Relevance
“…The 133 included studies collectively reported on more than 9.1 million surgical procedures (median per study, 894 [IQR, 97-4259]) and more than 11.4 million participants (median per study, 989 [IQR, 257-6857]) from 63 LMICs . Of all 133 LMICs, we found studies from 15 of all 29 low-income countries (51.7%), 25 of all 50 lower-middle–income countries (50.0%), and 23 of all 55 upper-middle–income countries (41.8%) . Fourteen studies (10.5%) were multinational …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 133 included studies collectively reported on more than 9.1 million surgical procedures (median per study, 894 [IQR, 97-4259]) and more than 11.4 million participants (median per study, 989 [IQR, 257-6857]) from 63 LMICs . Of all 133 LMICs, we found studies from 15 of all 29 low-income countries (51.7%), 25 of all 50 lower-middle–income countries (50.0%), and 23 of all 55 upper-middle–income countries (41.8%) . Fourteen studies (10.5%) were multinational …”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies (10.5%) were multinational . Of the 119 studies (89.5%) originating from single countries, 69 (58.0%) were from upper-middle–income countries and 30 (25.2%) were from East Asia and the Pacific (Table 1 and Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations